A multi-dimensional EBP educational program to improve evidence-based practice and critical thinking of hospital-based nurses: Development, implementation, and preliminary outcomes. (March 2021) - Liu, Meiling; Lin, Yan; Dai, Ying; Deng, Yongfang; Chun, Xiao; Lv, Yunxia; Yang, Hongmei; He, Fang
Abstract: Improving outcomes and quality of care through evidence-based practice (EBP) is a priority globally. But most nurses have insufficient competence in EBP. How to conduct Educational interventions to enhance clinical nurses' EBP competencies and critical thinking disposition (CTD) requires more evidence. One hundred eleven clinical nurses from a Chinese four-campus hospital were enrolled in our EBP education program. The Johns Hopkins Nursing Evidence-Based Practice Model was used to develop and guide the educational and practical sessions. Multi-dimensional learning strategies —including online self-learning, on-site lectures, workshops, and social media-facilitated group discussions—were used to facilitate the implementation of the education sessions. After education, nurses embedded evidence into practice. The Chinese versions of the EBP Believe scale (EBPB), EBP Implementation scale (EBPI), and the Simplified Chinese Version of the Critical Thinking Disposition Inventory (CTDI-SCV) were applied to assess the relevant competencies among clinical nurses before and after the education program. Clinical nurses' EBPB, EBPI, and CTDI-SCV scores improved. But only EBPB and EBP skills and attitudes were enhanced with a statistical difference ( t  = −2.980, −4.141, and −2.695, with all p  < 0.01). There was a small positive association between EBPB and CTDI-SCV (r = 0.396, p < 0.01). Fifteen EBP programs were successfully accomplished. Highlights: One hundred and eleven nurses from a Chinese four-campus hospital were included in the EBP education program. Multidimensional EBP education could enhance clinical nurses' EBPB, skills and positive attitude. Fifteen EBP programs were successfully conducted after the multidimensional EBP educational program. Multidimensional EBP education in this program was less effective in cultivating their CTD.